2005
DOI: 10.4102/ojvr.v72i2.217
|View full text |Cite
|
Sign up to set email alerts
|

Survey of nematophagous fungi in South Africa : research communication

Abstract: <span style="font-family: arial,helvetica;">Three hundred and eighty-four samples of leaf litter, soil, faeces from domestic and game animals, compost and aqueous cultures of infective nematode larvae contaminated with unidentified fungi were plated out on water agar, baited with pure infective larvae of <em>Haemonchus contortus</em>, incubated and examined for the presence of nematophagous fungi. <br /><em>Duddingtonia flagrans</em> was isolated from five samples, and 73 sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Another possible reason may be related to its high saprophytic ability and the increased agricultural intensification caused by soil disturbance and the addition of fertilizers. Similar results have been reported in South Africa [32,33], Kenya [34,35], China [14,[36][37][38], and Oman [39]. The greatest diversity of nematophagous fungi species was recorded in midland (Bishoftu).…”
Section: Discussionsupporting
confidence: 85%
“…Another possible reason may be related to its high saprophytic ability and the increased agricultural intensification caused by soil disturbance and the addition of fertilizers. Similar results have been reported in South Africa [32,33], Kenya [34,35], China [14,[36][37][38], and Oman [39]. The greatest diversity of nematophagous fungi species was recorded in midland (Bishoftu).…”
Section: Discussionsupporting
confidence: 85%
“…However, a nematode-killing fungus, Duddingtonia flagrans, discovered in New Zealand (Skipp et al 2002), showed a trapping efficiency rate of 78% and activity for up to 90 days on pasture, providing a viable alternative to reduce animal mortality from nematode infections (Waghorn et al 2003). Surveys in neighbouring South Africa have shown the presence of local strains of D. flagrans (Durand et al 2005). Given the limited genetic variation between isolates from different parts of the world (Faedo 2001), a survey of Zimbabwean local strains would address any concerns regarding importing a foreign fungus.…”
Section: Pasture Management Biological Control and Nutrient Supplementationmentioning
confidence: 99%
“…Studies performed on different countries demonstrated the presence of nematophagous fungi in fecal samples from domestic animal species [ 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%